Problems of Implementation of the Rights of the Child in Lithuania - Jonynienė, Živilė (Acta Paedagogica Vilnensia, 2005)
Article focuses on review and investigation of development and problems of implementation of the rights of the Child in Lithuania. Since 2000, the real reform of the General Measures of implementation of children’s rights has started - adopted, amended or supplemented many specified legal acts, projects and national programs. Reform of General measures requires the review and reorganization of activities in social work with a child. The task of the article is to reveal the main problems of the implementation of Children’s rights by investigation of the documents, opinions of child protection experts, and experience of children in the field. The research comprises ideas of child protection experts on the main things that have to be done to promote the implementation and protection of the rights of the child. Also, the main problem that social workers deal with in child protection – child abuse – has been investigated exploring abuse in the family experience of school children. Research results show that experts of child protection (92 percent. of resp.) think the child Iaw has not come into effect because of experts’ are not competent enough in the law and psychology, lack of human and material resources. 53 proc. of children questioned experience emotional abuse at home – mockery, critics. One third of children reply they experience physical violence in the family. Child abuse is rarer in the families better social characteristics - higher material welfare, parents are well educated, employed, and free of alcohol abuse. Research results reveal that abuse and punishment experience correlate with the social characteristics of the child, such as liking associate with people, openness, popularity in the peer group. The knowledge of the reasons and the consequences of the child abuse enables promote the principles of children’s rights in the society. According to the research results, adult education, family financial strengthening and development of capacities of the child protection structures are the main questions that need attention and many things to be done there.